Confinement size determines the architecture of Ran-induced microtubule networks. Issue 24 (27th May 2021) - Gai, Ya; Cook, Brian; Setru, Sagar; Stone, Howard A.; Petry, Sabine
Abstract : By using microfluidics to encapsulate mitotic extracts, we show that both microtubule nucleation and physical confinement play critical roles in determining the spatial organization of the microtubule cytoskeleton. Abstract : The organization of microtubules (MTs) is critical for cells during interphase and mitosis. During mitotic spindle assembly, MTs are made and organized around chromosomes in a process regulated by RanGTP. The role of RanGTP has been explored in Xenopus egg extracts, which are not limited by a cell membrane. Here, we investigated whether cell-sized confinements affect the assembly of RanGTP-induced MT networks in Xenopus egg extracts. We used microfluidics to encapsulate extracts within monodisperse extract-in-oil droplets. Importantly, we find that the architecture of Ran-induced MT networks depends on the droplet diameter and the Ran concentration, and differs from structures formed in bulk extracts. Our results highlight that both MT nucleation and physical confinement play critical roles in determining the spatial organization of the MT cytoskeleton.